Maternal Blood Pressure During Pregnancy and Early Childhood Blood Pressures in the Offspring: The GUSTO Birth Cohort Study. Issue 45 (November 2015) - Lim, Wai-Yee; Lee, Yung-Seng; Yap, Fabian Kok-Peng; Aris, Izzudin Mohd; Ngee, Lek; Meaney, Michael; Gluckman, Peter D.; Godfrey, Keith M.; Kwek, Kenneth; Chong, Yap-Seng; Saw, Seang-Mei; Pan, An
Abstract : Abstract: Although epidemiological studies suggest that offspring of women with preeclampsia are at increased risk to higher blood pressures and cardiovascular disease, little is known about the nature of blood pressures between the mother and her offspring. As blood pressures comprise of both pulsatile (systolic blood pressure [SBP] and pulse pressure [PP]) and stable (diastolic blood pressure [DBP]) components, and they differ between central and peripheral sites, we sought to examine maternal peripheral and central blood pressure components in relation to offspring early childhood blood pressures. A prospective birth cohort of 567 Chinese, Malay, and Indian mother–offspring with complete blood pressure information were studied. Maternal brachial artery SBP, DBP, and PP were measured at 26 to 28 weeks gestation; and central SBP and PP were estimated from radial artery waveforms. Offspring brachial artery SBP, DBP, and PP were measured at 3 years of age. Associations between continuous variables of maternal blood pressures (peripheral SBP, DBP, PP, central SBP, and PP) and offspring blood pressures (peripheral SBP, DBP, and PP) were examined using multiple linear regression with adjustment for maternal characteristics (age, education level, parity, smoking status, alcohol consumption and physical activity during pregnancy, and pre-pregnancy BMI) and offspring characteristics (sex, ethnicity, BMI, and height at 3 years of age). In the multivariate models, offspring peripheral SBP increased by 0.08 (95% confidence interval 0.00–0.17, P  = 0.06) mmHg with every 1-mmHg increase in maternal central SBP, and offspring peripheral PP increased by 0.10 (0.01–0.18, P  = 0.03) mmHg for every 1-mmHg increase in maternal central PP. The relations of maternal-offspring peripheral blood pressures (SBP, DBP, and PP) were positive but not statistically significant, and the corresponding values were 0.05 (−0.03 to 0.13; P  = 0.21), 0.03 (−0.04 to 0.10; P  = 0.35), and 0.05 (−0.02 to 0.13; P  = 0.14), respectively. Maternal central pulsatile blood pressure components (SBP and PP) during pregnancy are associated with higher blood pressures in the offspring. This positive correlation is already evident at 3-years old. Studies are needed to further evaluate the effects of maternal central pulsatile blood pressure components during pregnancy and long-term cardiovascular health in the offspring. Abstract : Supplemental Digital Content is available in the text